2012
DOI: 10.5601/jelem.2013.18.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and pools of trace elements in organic soils in the Izera Mountains

Abstract: Concentrations of trace elements in organic soils are a result of natural accumulation or due to anthropogenic factors. A field study was carried out in May 2008 on selected sites in the Izera Mountains. Soil samples were collected from 8 profiles of organic soils. Four soil profiles were located on the plateau meadow called Hala Izerska, at the altitude of 835-850 m a.s.l. The other 4 profiles were located in the mountain range known as the Grzbiet Wysoki, at 909-990 m a.s.l. The concentration and pools of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…3), indicated that concentrations of this trace elements in studied soils is the result of atmospheric deposition. Similar observation were reported for organic soils from different area in Europe [2,5,6]. Also, fluvial origin of Pb and Zn is possible here, what was confirmed by statistical analysis.…”
Section: Trace Elements Concentrationssupporting
confidence: 91%
“…3), indicated that concentrations of this trace elements in studied soils is the result of atmospheric deposition. Similar observation were reported for organic soils from different area in Europe [2,5,6]. Also, fluvial origin of Pb and Zn is possible here, what was confirmed by statistical analysis.…”
Section: Trace Elements Concentrationssupporting
confidence: 91%
“…Trace element deposition in soil can result from anthropogenic factors and from natural accumulation. Polluted wastewater and air are potential sources of heavy metal contamination in the soil environment (cHarY et al 2008, HuanG et al 2009, sienkiewicz, czarneckaet al 2012, Glina, BoGacz 2013, wanG et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…1 0 5 -0 3 4 Organic horizons in many part of Sudetes Mountains showed a higher content of lead compared to zinc. This observation was related mainly to the Izera (Bogacz 2005;Glina and Bogacz 2013) and Sto³owe Mountains (Glina et al 2017b). This is, according to Strzyszcz and Magiera (2001), proof of the transport of contaminants over long distances.…”
Section: Resultsmentioning
confidence: 77%
“…The interference in hydrological stability of peatland has often led to many changes in wetland soil properties (Bogacz 2005;Kucharczyk and Szary 2012;Glina et al 2016b, Glina et al 2019. The concentration and pools of trace elements could be also connected with peat soil transformation (Kaba³a and Szerszeñ 1998;Glina and Bogacz 2013;Glina et al 2016cGlina et al , 2017b. The aim of this paper was to assess the variability of the concentrations of trace elements pools in two analysed layers (0-30 cm) and (30-50 cm) in organic soils of the previously pristine peatland partially transformed by human activities (drainage, and peat extraction).…”
Section: Introductionmentioning
confidence: 99%